(untitled) (Journal of Forensic Medicine & Toxicology, 2015)
Although popularly considered as a modern utility, the study of fingerprints and skin ridge patterns is probably the oldest of all sciences. Fingerprints once formed remain permanent and never change throughout the life. The present study includes 150 cases of angiographically proven myocardial infarction patients and 150 cases of healthy normal individuals. The fingerprints of both hands were taken by plain and rolled method on white paper to determine the correlation between fingertip patterns and myocardial infarction. It is noted that there is significant decrease in loops in thumb in males with significant increase in whorls in little finger in males, and thumb and little finger in left hand in myocardial infarction patients. Also there is significant decrease in arches in little finger in males and thumb in females with significant increase in arches in little finger in females in myocardial infarction patients. Moreover, there is significant decrease in loops with corresponding increase in whorls in males, (M+F) combined series and left hand of myocardial infarction patients as compared to the controls. The mean value of finger ridge count in myocardial infarction patients is increased in both sexes but not significant. Thus, apart from its use in forensic science for identification and disputed paternity, fingerprint can also be use in predicting the myocardial infarction in healthy individual at an earlier age.